Find arsinh(x) in terms of x

let y=arsinh(x)x=sinh(y)=(ey - e-y)/22x=e- e-y2x*ey=ey-1 (multiply byey)0=(ey)2-2xey-1This is a quadratic in ey with coefficients: a=1,b=-2x,c=-1Usinng the quadratic formula (and simplifying):e^y=x +/- sqrt(x2+1)but ey=x-sqrt(x2+1) isn't possible as ey>0 for all y.so ey=x+sqrt(x2+1)y=ln(x+sqrt(x2+1))arsinh(x)=ln(x+sqrt(x2+1)).(Note that sqrt(x) is standard notation for 'the square root of x' on computers).

Related Further Mathematics A Level answers

All answers ▸

Express f(x) = ln(x+1) as an infinite series in ascending powers of x up to the 3rd power of x


By Differentiating from first principles, find the gradient of the curve f(x) = x^2 at the point where x = 2


If the complex number z = 5 + 4i, work out 1/z.


How can I find the explicit formula for the inverse of sinh?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences